Computational Approaches in Cheminformatics and Bioinformatics. - Guha, Rajarshi (John Wiley & Sons, 2012)
A breakthrough guide employing knowledge that unites cheminformatics and bioinformatics as innovation for the futureBridging the gap between cheminformatics and bioinformatics for the first time, Computational Approaches in Cheminformatics and Bioinformatics provides insight on how to blend these two sciences for progressive research benefits. It describes the development and evolution of these fields, how chemical information may be used for biological relations and vice versa, the implications of these new connections, and foreseeable developments in the future. Using algorithms and domains.